A Study of Innovative HR Practices and Business Performance: Case of SMEs from AlDakliya Region, Oman - Kutpudeen, Mohammed; Tahir, Muhammad; AlNabhani, Hajar Saud Muhanaa; Ahmed, Naseema; Al-Arini, Ahlam Eid Ghashim; Al-Fahdi, Buthaina Saif; Al-Hashmi, Raid Sultan; Al-Wardi, Shahad Ibrahim (Advances in Social Sciences Research Journal, 2022)
In a current dynamic business environment, human resources is playing a pivotal role in organizational effectiveness. The success of any organization regardless of the size is largely depended on the effective management of the human resource. This study attempted to study the impact of Innovative Human Resource Management Practices (IHRP) in Small and Medium enterprises in Oman, particularly in the Al-Dhakiliya governorate. We used the Cluster analysis to collect data from five major industrial areas of the region to study the level of adoption of innovative human resource practices (IHRP) and to analyze how the practices are associated with the outcomes of HR and the firms’ performance. It is found that innovation in talent acquisition, compensation systems, and learning and development practices significantly influenced the performance of firms. The degree to which SMEs have adopted innovative human resource practices is shown to be closely related to human resource outcomes and firm performance.